New Quantitative Structure–Activity Relationship Models Improve Predictability of Ames Mutagenicity for Aromatic Azo Compounds. (13th July 2016) - Manganelli, Serena; Benfenati, Emilio; Manganaro, Alberto; Kulkarni, Sunil; Barton-Maclaren, Tara S.; Honma, Masamitsu
Abstract: Existing Quantitative Structure–Activity Relationship (QSAR) models have limited predictive capabilities for aromatic azo compounds. In this study, 2 new models were built to predict Ames mutagenicity of this class of compounds. The first one made use of descriptors based on simplified molecular input-line entry system (SMILES), calculated with the CORAL software. The second model was based on the k -nearest neighbors algorithm. The statistical quality of the predictions from single models was satisfactory. The performance further improved when the predictions from these models were combined. The prediction results from other QSAR models for mutagenicity were also evaluated. Most of the existing models were found to be good at finding toxic compounds but resulted in many false positive predictions. The 2 new models specific for this class of compounds avoid this problem thanks to a larger set of related compounds as training set and improved algorithms.